A rare loss-of-function variant of ADAM17 is associated with late-onset familial Alzheimer disease - Hartl, Daniela; May, Patrick; Gu, Wei; Mayhaus, Manuel; Pichler, Sabrina; Spaniol, Christian; Glaab, Enrico; Bobbili, Dheeraj Reddy; Antony, Paul; Koegelsberger, Sandra; Kurz, Alexander; Grimmer, Timo; et al. (Nature Publishing Group, 2018)
Common variants of about 20 genes contributing to AD risk have so far been identified through genome-wide association studies (GWAS). However, there is still a large proportion of heritability that might be explained by rare but functionally important variants. One of the so far identified genes with rare AD causing variants is ADAM10. Using whole-genome sequencing we now identified a single rare nonsynonymous variant (SNV) rs142946965 [p.R215I] in ADAM17 co-segregating with an autosomal-dominant pattern of late-onset AD in one family. Subsequent genotyping and analysis of available whole-exome sequencing data of additional case/control samples from Germany, UK, and USA identified five variant carriers among AD patients only. The mutation inhibits pro-protein cleavage and the formation of the active enzyme, thus leading to loss-of-function of ADAM17 alpha-secretase. Further, we identified a strong negative correlation between ADAM17 and APP gene expression in human brain and present in vitro evidence that ADAM17 negatively controls the expression of APP. As a consequence, p.R215I mutation of ADAM17 leads to elevated Aß formation in vitro. Together our data supports a causative association of the identified ADAM17 variant in the pathogenesis of AD.